2003
DOI: 10.1213/01.ane.0000087066.71572.3f
|View full text |Cite
|
Sign up to set email alerts
|

The Antiinflammatory and Analgesic Effects of Baicalin in Carrageenan-Evoked Thermal Hyperalgesia

Abstract: Our results showed that baicalin possesses an analgesic effect in carrageenan-evoked thermal hyperalgesia. The possible mechanisms of action of baicalin may be associated with the inhibition of proinflammatory mediator overproduction, including cytokines, nitric oxide, and prostaglandin E(2), as well as neutrophil infiltration. This implies that baicalin may be a potential therapeutic analgesic for inflammatory pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 21 publications
2
82
0
2
Order By: Relevance
“…As a result of our study, we previously reported that several natural compounds affected mucin secretion by airway epithelial cells (Lee et al, 2003;Heo et al, 2006;Heo et al, 2007). According to a number of reports, Scutellariae Radix has been used to control airway allergic or inflammatory diseases, and their components, baicalin and baicalein, were reported to have diverse biological effects (Chou et al, 2003;Dong et al, 2005;Van Leyen et al, 2006;Hsieh et al, 2007). Baicalein was reported to be a potent antioxidant and free radical scavenger and has been regarded as a 12/15-lipoxygenase inhibitor and xanthine oxidase inhibitor (Van Leyen et al, 2006).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…As a result of our study, we previously reported that several natural compounds affected mucin secretion by airway epithelial cells (Lee et al, 2003;Heo et al, 2006;Heo et al, 2007). According to a number of reports, Scutellariae Radix has been used to control airway allergic or inflammatory diseases, and their components, baicalin and baicalein, were reported to have diverse biological effects (Chou et al, 2003;Dong et al, 2005;Van Leyen et al, 2006;Hsieh et al, 2007). Baicalein was reported to be a potent antioxidant and free radical scavenger and has been regarded as a 12/15-lipoxygenase inhibitor and xanthine oxidase inhibitor (Van Leyen et al, 2006).…”
Section: Introductionsupporting
confidence: 51%
“…Baicalein has been shown to antagonize the expression of adhesion molecules induced by interleukin-β1 (IL-β1) and tumor necrosis factor (TNF-α) (Hsieh et al, 2007). Baicalin demonstrated anti-inflammatory and analgesic effects through the inhibition of important inflammatory mediators and proinflammatory cytokines, as well as through neutrophil infiltration at sites of inflammation (Chou et al, 2003). Inhalation of baicalin showed an inhibition of airway hyperresponsiveness (Dong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, many species of Tephrosia genus present flavonoids (Arriaga et al, 2009a;Arroio et al, 2004;Jang et al, 2003). There is evidence that isolated flavonoids reduce mechanical and thermal hyperalgesia (e.g., increased response to nociceptive stimuli; pain) by activating the endogenous opioid system (Anjaneyulu & Chopra, 2003;Delporte et al, 2007;Loscalzo et al, 2008Loscalzo et al, , 2011 and inhibition of hyperalgesic cytokines production (Chou et al, 2003;Kandhare et al, 2012;Valério et al, 2009b;Valsecchi et al, 2008).…”
Section: Introductionmentioning
confidence: 69%
“…Previous reports suggested that baicalin could inhibit tissue's inflammatory response through decreasing the release of TNF-α, IL-1 β, IL-6 and other factors which had been confirmed that might enhance osteoclast function and promote bone resorption directly or indirectly [11][12][13]. Wang GF [26] showed that the expression of RANKL mRNA stimulated by IL-1β was inhibited by baicalin after being treated for 12h and the inhibition reached its maximum at 48h.…”
Section: Discussionmentioning
confidence: 89%
“…Baicalin is a flavonoid purified from the medicinal plant Scutellariabaicalensi Georgi that has been used in herbal formulas to treat inflammatory diseases for thousands of years in traditional Chinese medicine. It had been reported that baicalin exhibited antibacterial, anti-inflammatory and analgesic effects [5][6][7][8][9][10]. Many scholars found that baicalin could inhibit tissue's inflammatory response through decreasing the release of TNF-α, IL-1 β, IL-6 and other factors which had been confirmed that might enhance osteoclast function and promote bone resorption directly or indirectly [11][12][13].…”
Section: Introductionmentioning
confidence: 97%